Bridging health professional and communities through innovation - Bakri, Noor Nazahiah; Yusof, Norashikin (UUM Press, 2020)
Bridging Health Professional and Communities Through Innovation is a book showcasing the innovative works from different teams of oral health and non-oral health professionals primarily to the practicing dentists, postgraduate and undergraduate dental students aimed to introduce different innovations and inventions related to the field of dentistry. Each chapter in this book begin with a discussion of some limitations of current methods of oral health care practice and suggest innovative measures to deal with the limitations, that can be applied at different levels of the health care system care-system from the patient care experience to the broader system. It is a compilation of creative and innovative works from improved clinical care practice such as ‘The Minimalist Surgical Drape’ to impactful community oral health care empowerment as in ‘The Bario Experience’. It is hoped that the methods introduced in this book promote a safe and effective treatment option for patients and the community, thus providing the best patient care and practice.